Estimates of the prevalence of speech and motor speech disorders in adolescents with Down syndrome - Wilson, Erin M. (Clin Linguist Phon, 2019)
Although there is substantial rationale for a motor component in the speech of persons with Down syndrome (DS), there presently are no published estimates of the prevalence of subtypes of motor speech disorders in DS. The goal of this research is to provide initial estimates of the prevalence of types of speech disorders and motor speech disorders in adolescents with DS. Conversational speech samples from a convenience sample of 45 adolescents with DS, ages 10 to 20 years old, were analysed using perceptual and acoustic methods and measures in the Speech Disorders Classification System (SDCS). The SDCS cross-classified participants into five mutually exclusive speech classifications and five mutually exclusive motor speech classifications. For participants meeting criteria for Childhood Dysarthria or for Childhood Dysarthria concurrent with Childhood Apraxia of Speech, the SDCS provided information on participants’ percentile status on five subtypes of dysarthria. A total of 97.8% of participants met SDCS criteria for Speech Disorders and 97.8% met criteria for Motor Speech Disorders, including Childhood Dysarthria (37.8%), Speech Motor Delay (26.7%), Childhood Dysarthria and Childhood Apraxia of Speech (22.2%), and Childhood Apraxia of Speech (11.1%). Ataxia was the most prevalent dysarthria subtype. Nearly all participants with DS in the present sample had some type of speech and motor speech disorder, with implications for theory, assessment, prediction, and treatment. Specific to treatment, the present findings are interpreted as support for motor speech disorders as a primary explanatory construct to guide the selection and sequencing of treatment targets for persons with DS.